Estudo bibliográfico das atitudes e comportamentos ligados à prostituição da Pré-História aos dias atuais - Rebolho, Ana Claudia Figueiredo [UNESP] (2015)
Prostitution is one of the oldest social phenomena known. It can be analyzed through several historical documents and it was highlighted by specific characteristics from different times and cultures. There have always been prostitutes in the world. Prostitutes were admired because of their intelligence and culture. They were also compared to goddesses by men who used to think that having sex with such women would make them be more respected by other men. However, their social status has changed from respectable to reprehensible. Nowadays, people do not see prostitutes as a good thing for society. Based on those changes through the years, it is necessary to study more about this subject without any prejudice because its complexity is related to taboos and social rules. As a methodological procedure, bibliographic research was used as a resource. The theoretical background was the authors who analyzed women's conditions through several aspects like sex, sexuality and prostitution. We had a great concern in not getting disconnected from the present reality, giving voice to the prostitutes through biographic books written by the prostitutes themselves, which served as a basis for comparison with what is presented by the scientific literature. As an attempt to greater historical comprehension of this subject, the main goal of this study is to analyze and describe the route of prostitution in human history. Along the research and analysis process, we could find a great deal of works which deal with the issue of prostitution in the health area (STD, AIDS, HPV), the legal area ( professionalization of prostitution), the historical area (analysis of historical documents about the prostitutes relating them to the women's history) and study cases of specific populations (prostitutes of the north and northeast regions of Brazil due to the poor economic situation of such regions). Although there are many studies...